Echocardiographic evaluation of univentricular physiology and cavopulmonary shunts. Issue 7 (27th June 2019) - Buber, Jonathan; Schwaegler, Rebecca Gibbons; Mazor Dray, Efrat
Abstract: Since the surgical palliation of a univentricular congenital heart defect was first described in the early 1970s, thousands of lives were saved by this groundbreaking operation. Although initially described for the palliation of tricuspid valve atresia, the Fontan operation is now utilized for many other univentricular heart defects involving either hypoplastic right or left ventricles, and the number of babies who survive the surgery and the postsurgical hospitalization continues to grow. Echocardiography constitutes the mainstay follow‐up imaging modality for patients with a Fontan system. In order to obtain all the needed information from the echocardiographic studies, close familiarity with the native congenital heart defects, the build of the Fontan systems, and the potential long‐term complications is required. Detailed studies provide valuable information on the various components of the Fontan circulation such as the function of the single ventricle and the valves, flow in the Glenn and Fontan pathways, and possible sources of cyanosis and shunts. Three‐dimensional and transesophageal echocardiogram studies can assist in delineating the Fontan anatomy and to evaluate smaller intracardiac structures.